Überlastungen des Schultergelenks und Fehlbelastungsfolgen am Ellenbogen - Pieper, H.-G. (Sport-Orthopädie - Sport-Traumatologie, 2002)
Chronic shoulder or elbow pain is not uncommon in overhead athletes, especially in ball sports (throwing sports such as baseball or team handball, but also contact sports such as American football, rugby or soccer). The reason is less frequently an acute trauma through fall or influence of an opponent, but much more often the result of repetitive microtrauma on capsule, ligaments or tendons by way of extreme cocking or acceleration respectively. As a result of chronic strain slight instability of the shoulder joint develops over time, which again might lead to secondary subacromial pain syndromes or to increased strain on the posterior or superior labrum. The so-called Thrower's Elbow is an inflammation of the flexor tendons at the epicondylar insertion (ulnar epicondylitis). This kind of tendinitis or tendinosis is frequently to be found in baseball pitchers or team handball players.